Lasers, Sources and Related Photonic Devices 2010
DOI: 10.1364/assp.2010.amb13
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Ho:YAG Laser in-band Pumped by Laser Diodes at 1.9 μm and Wavelength-Stabilized by a Volume Bragg Grating

Abstract: The first high-power Ho:YAG laser wavelength-stabilized by a volume Bragg grating is reported. A maximum output power of 15 W and a slope-efficiency of 37 % were achieved using in-band diode pumping. The spectrum of the Ho:YAG laser showed a stable narrow bandwidth operation. In free-running operation a maximum output power of 46 W and a slope efficiency of 62 % were achieved. The emitted wavelength of the free-running laser was 2118 nm and 2096 nm in wavelength-stabilized operation. In freerunning Q-switched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In 2010, Lamrini reported a 6.2 mJ Ho:YAG laser pumped by 160 W GaSb LD. In the next several years, 33 mJ Ho:YAG and 8 mJ Ho:Lu 2 O 3 lasers were reported by Lamrini [6][7][8]. In 2015, Berrou reported a Ho:YAG laser pumped by a 1.9 µm fiber-coupled laser diode, with output energy of 9 mJ [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Lamrini reported a 6.2 mJ Ho:YAG laser pumped by 160 W GaSb LD. In the next several years, 33 mJ Ho:YAG and 8 mJ Ho:Lu 2 O 3 lasers were reported by Lamrini [6][7][8]. In 2015, Berrou reported a Ho:YAG laser pumped by a 1.9 µm fiber-coupled laser diode, with output energy of 9 mJ [9].…”
Section: Introductionmentioning
confidence: 99%
“…Diode-pumped Tm-doped bulk lasers [4][5][6] and Tm-doped fiber lasers [7,8] turn out to be attractive sources for direct pumping of Ho:YAG lasers. Recently, a Ho:YAG laser directly pumped by laser diode stack at 1.9 μm was demonstrated [9][10][11]. So et al reported a slope efficiency of 60% in a Ho:YAG laser pumped by Tm-slab lasers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Holmium doped solid state laser sources in the ∼ 2 µm wavelength range are of interest for a variety of applications including range finding, laser radar, medicine and generation of 3 -5 µm mid-infrared laser sources via nonlinear frequency conversion [1]. Conventionally, YAG and YLF single crystals are among the most commonly used host materials owing to their robust thermo-mechanical and spectroscopic properties that favoring efficient laser operation [2][3][4][5][6]. In recent years, lutetium aluminum garnet (Lu 3 Al 5 O 12 or LuAG), an isomorph of YAG, has drawn great attention as a promising new host material due to a number of advantages over other garnet host materials [7][8][9].…”
Section: Introductionmentioning
confidence: 99%